The aging effect on prostate metabolite concentrations measured by 1H MR spectroscopy - Dezortova, Monika; Jiru, Filip; Skoch, Antonin; Capek, Vaclav; Ryznarova, Zuzana; Vik, Viktor; Hajek, Milan (Magma (New York, N.Y.), 2017)
OBJECTIVE: The effects of aging, magnetic field and the voxel localization on measured concentrations of citrate (Cit), creatine (Cr), cholines (Cho) and polyamines (PA) in a healthy prostate were evaluated. MATERIALS AND METHODS: 36 examinations at both 1.5T and 3T imagers of 52 healthy subjects aged 19-71 years were performed with PRESS 3D-CSI sequences (TE = 120 and 145 ms). Concentrations in laboratory units and their ratios to citrate were calculated using the LCModel technique. Absolute concentrations were also obtained after the application of correction coefficients. Statistical analysis was performed using a robust linear mixed effects model. RESULTS: Significant effects of aging, the magnetic field strength and the voxel position in central (CZ) or peripheral (PZ) zones on all measured metabolites were found. The concentrations (mmol/kg wet tissue) including prediction intervals in a range of 20-70 years were found: Cit: 7.9-17.2; Cho: 1.4-1.7; Cr: 2.8-2.5; PA (as spermine): 0.6-2.1 at 3T in CZ. In PZ, the concentrations were higher by about 10 % as compared to CZ. CONCLUSION: Increasing citrate and spermine concentrations with age are significant and correlate well with a recently described increase of zinc in the prostate. These findings should be considered in decision-making if the values obtained from a subject are in the range of control values.
Keywords: Prostatic Neoplasms; 1H MRS; prostata; nádory prostaty; Spermine; Humans; lidé středního věku; Choline; kreatinin; citráty; Decision Making; Aged; mladý dospělý; dospělí; spermin; rozhodování; Zinc; senioři; lidé; magnetické pole; magnetická rezonanční spektroskopie; Creatinine; cholin; zinek; Aging; Creatine; Adult; Citrates; Male; Prostate; Middle Aged; Citrate; Young Adult; polyaminy; Magnetic Resonance Spectroscopy; Magnetic Fields; mužské pohlaví; Polyamines